Momentousness of the mental loop: A comparative study - Ramya Katyayani Kastala; Chaya Manoranjini David; Namitha Jayapal (Wolters Kluwer Medknow Publications, 2019)
Background and Purpose: To assess the anterior (aAL) and caudal (cAL) extensions of Anterior loop (AL) of Inferior alveolar nerve (IAN) using Digital Panoramic (DP) and Cone Beam Computed Tomography (CBCT) for its presence and dimensions in various age groups, genders, right and left sides of the mandible and between dentulous and edentulous patients. Methods: A 1-year retrospective comparative study between DP and CBCT to assess the extensions of AL of IAN was conducted on individuals referred to a private imaging center located in Bengaluru, South India. 360 mandibular sites were examined using DP and CBCT to assess the presence and dimensions of AL. Results: Results showed higher frequency of AL in CBCT compared to DP. Also there was a decreasing frequency of AL with increasing age and an insignificant difference in frequency between males and females. Bilateral looping was most common, aAL was more frequent on the left side and cAL on the right of the mandible. Statistically higher frequency in dentate group compared to edentulous. A decreasing mean value with increasing age and higher mean values in CBCT than DP. No significant difference in mean values among males and females or between the dentulous and edentulous groups. Higher mean values in CBCT compared to DP on the left side of the mandible compared to the right. Conclusion: Choosing mental foramen as reference for termination of IAN could result in injury to AL; low sensitivity and specificity of DP compared to CBCT in assessing frequency and extent of AL underlines its inadequacy, while CBCT can be performed with comparable resolution, to accurately analyze AL.